European structural funds and resilient and recovery facility governance - Carlos San Juan Mesonada; Carlos Sunyer Manteiga (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
The paper attempts to recover empirical evidence related to the European Structural and Investment Funds (ESIF) to promote growth for the management of the Recovery & Resilience Facility (RRF). We analyse the impact of the EU Cohesion Policy on regional development over the period 1986-2018, using dynamic panel data models. In doing so, we use a neoclassical Solow growth model, extending the current literature in at least three ways. First, we make use of a new dataset, which contains highly detailed data on regional commitments and payments of Structural Funds; secondly, we address the endogeneity via a difference GMM estimator; finally, we control for the spatial interdependence among regions via a Spatial Durbin model. We find that the Cohesion Policy fosters regional growth both in the short and long run, regardless of the Objective considered. The role of the business cycle in the speed of regional convergence is quantified. The funds' effectiveness is hindered during the crisis, especially in the least developed regions, partly due to lower absorptive rates. Furthermore, human capital and quality of government are crucial growth determinants necessary for improving the performance of the Structural Funds. Finally, we discuss if the combination of ESIF & RRF funds will be appropriate for accelerating the post-pandemic recovery versus the financial recession recovery.
Keywords: 330; Spatial panel econometrics; Generalised Method of Moments; EuropeanUnion; Regional economic growth; Structural Funds